Leg Lengthening as a Means of Improving Ambulation Following an Internal Hemipelvectomy - Wakyo Sato; Hiroshi Okazaki; Takahiro Goto (Case Reports in Orthopedics, 2016)
Reconstructive surgery following an internal hemipelvectomy for a malignant pelvic tumor is difficult due to the structural complexity of the pelvis and the massive extension of the tumor. While high complication rates have been encountered in various types of reconstructive surgery, resection without reconstruction reportedly involved fewer complications. However, this method often results in limb shortening with resultant instability during walking. We reported herein leg lengthening performed to correct lower limb shortening after an internal hemipelvectomy, which improved ambulatory stability and overall QOL. An 18-year-old male patient came to our hospital to correct a lower limb discrepancy resulting from a left internal hemipelvectomy. His left pelvis and proximal femur had been resected, and the femur remained without an acetabular roof. His left lower limb was about 8 centimeters shorter. The left tibia was lengthened 8 centimeters with an external fixator. After the lengthening, the patient was able to walk without support and his gait remarkably improved. Additionally he no longer required placing a wallet in his back pocket as a pad as a means of raising the left side of his torso while sitting. Leg lengthening was a useful method of improving ambulation after an internal hemipelvectomy.